RESEARCH ON THE TREND OF SUSTAINABLE ARCHITECTURE: A BIBLIOMETRIC ANALYSIS ON THE HOUSING, THERMAL COMFORT, AND FAÇADE - Suniarti Simanjuntak; Jesicha Darmawanti; Ratih Widiastuti; Chely Novia Bramiana (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2026)
Abstract: Sustainable architecture plays a crucial role in minimizing environmental impact and enhancing energy efficiency in buildings. This study aims to explore research trends in sustainable architecture, particularly in housing, thermal comfort, and façade design, using bibliometric analysis with VOSviewer. The data were retrieved from the leading academic databases (Scopus). The analysis was conducted on the study maps keyword relationships, author collaborations, and institutional influences through co-occurrence network. The findings highlighted a growing emphasis on passive design strategies, innovative façade technologies, and adaptive thermal comfort models to promote sustainability in housing. Further analysis identified the cluster key themes involved thermal comfort, housing, architectural design, energy efficiency, and thermal insulation. This research offers valuable insights to develop the sustainable architecture, providing a useful reference for architects, policymakers, and researchers looking to enchance energi-efficient housing designs yet still prioritizing occupant comfort. Keyword: bibliometric analysis, façade design, housing building, sustainable architecture, thermal comfort Abstrak: Arsitektur berkelanjutan memainkan peran penting dalam meminimalkan dampak lingkungan dan meningkatkan efisiensi energi pada bangunan. Penelitian ini bertujuan untuk mengeksplorasi tren penelitian dalam arsitektur berkelanjutan, khususnya pada bidang perumahan, kenyamanan termal, dan desain fasad, menggunakan analisis bibliometrik dengan VOSviewer. Data diperoleh dari basis data akademik terkemuka (Scopus). Analisis dilakukan untuk memetakan hubungan kata kunci, kolaborasi penulis, dan pengaruh institusional melalui jaringan ko-okurensi. Temuan penelitian menyoroti semakin besarnya penekanan pada strategi desain pasif, teknologi fasad inovatif, dan model kenyamanan termal adaptif untuk mendorong keberlanjutan dalam perumahan. Analisis lebih lanjut mengidentifikasi tema-tema utama kluster yang meliputi kenyamanan termal, perumahan, desain arsitektur, efisiensi energi, dan insulasi termal. Penelitian ini memberikan wawasan berharga untuk pengembangan arsitektur berkelanjutan, sekaligus menjadi referensi yang berguna bagi para arsitek, pembuat kebijakan, dan peneliti yang ingin meningkatkan desain perumahan hemat energi dengan tetap mengutamakan kenyamanan penghuni. Kata Kunci: analisis bibliometrik, desain fasad, bangunan perumahan, arsitektur berkelanjutan, kenyamanan termal